Rebelión campesina y cambio social / Henry Landsberger, ed.; Yu G. Alexandrov ... [et al.] - Landsberger, Henry A.Aleksandrov, IU. G. (IUrii Georgievich) (Serie general (Crítica). Estudios y ensayos)
Índices